2014
DOI: 10.1073/pnas.1408401111
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic rescue of an enzyme-trafficking defect in primary hyperoxaluria 1

Abstract: Significance The lethal disorder, primary hyperoxaluria 1 (PH1), is caused by mutations in peroxisomal-localized alanine:glyoxylate aminotransferase (AGT). AGT contains a C-terminal peroxisomal targeting sequence, but mutations generate a strong N-terminal mitochondrial targeting sequence that directs AGT to mitochondria. Although mutant AGT is functional, the enzyme must be in the peroxisome to detoxify glyoxylate and prevent oxalate accumulation. We have identified a Food and Drug Administration-ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 30 publications
1
56
0
Order By: Relevance
“…Both the administration of oxalate-degrading bacteria and gene therapy have been identified as suitable strategies. Moreover, recent in vitro results have indicated that dequalinium chloride, a compound already approved by the Food and Drug Administration, is able to counteract the AGT mistargeting caused by the G170R mutation, the most common one causing PH1 [26][27][28].…”
Section: Primary Hyperoxaluria Type Imentioning
confidence: 99%
See 1 more Smart Citation
“…Both the administration of oxalate-degrading bacteria and gene therapy have been identified as suitable strategies. Moreover, recent in vitro results have indicated that dequalinium chloride, a compound already approved by the Food and Drug Administration, is able to counteract the AGT mistargeting caused by the G170R mutation, the most common one causing PH1 [26][27][28].…”
Section: Primary Hyperoxaluria Type Imentioning
confidence: 99%
“…However, each approach explores a different facet of a mutation's effect. Expression in mammalian cells is considered as the closest model of in vivo conditions and gives information on the expression level, intracellular stability and targeting of the AGT variants [17,28,35,40,[46][47][48][49][50]. On the other hand, the purification and characterization of the variants expressed in E. coli are suitable to dissect and quantify the effect of a mutation on the functional properties of AGT as well as on its secondary, tertiary and quaternary structures [11][12][13]17,18,35,36,[51][52][53][54][55][56][57][58].…”
Section: A Comprehensive Analysis Of the Molecular And Cellular Effecmentioning
confidence: 99%
“…The thought-provoking discovery that individual mitochondrial proteins have widely differing half-lives raises questions about the mechanisms governing this process; regulation of these different mechanisms for degrading mitochondrial proteins may be quite complex, and their contribution to disease phenotypes will be equally so. The importance of mitochondrial protein import is emerging: recently it was reported that redirecting a mutant form of alanine:glyoxalate aminotransferase from mitochondria to peroxisomes corrects primary hyperoxaluria 1 (PH1), a lethal metabolic disease [176]. Enzymes that may traffic either to mitochondria or peroxisomes can have radically different consequences depending on their location; the potential significance of this process for heart disease is unknown at present.…”
Section: Prospects and Challenges For The Futurementioning
confidence: 99%
“…In fact, other B6 vitamers, such as pyridoxamine (PM) and pyridoxal (PL), could be more effective than pyridoxine (PN) (Oppici et al 2015), and ongoing studies are trying to improve the therapeutic benefit that could derive from these types of molecules. In addition, various screenings with small molecules have resulted in some hits that seem to revert the mitochondrial mistargeting, at least in vitro (Miyata et al 2014;Madoux et al 2015).…”
Section: Chaperone-proteostasis Regulator Therapy (Cprt)mentioning
confidence: 99%